Role of the A2B receptor–adenosine deaminase complex in colonic dysmotility associated with bowel inflammation in rats. (March 2014) - Antonioli, L; Fornai, M; Awwad, O; Giustarini, G; Pellegrini, C; Tuccori, M; Caputi, V; Qesari, M; Castagliuolo, I; Brun, P; Giron, M C; Scarpignato, C; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose Adenosine A2B receptors regulate several physiological enteric functions. However, their role in the pathophysiology of intestinal dysmotility associated with inflammation has not been elucidated. Hence, we investigated the expression of A2B receptors in rat colon and their role in the control of cholinergic motility in the presence of bowel inflammation. Experimental Approach Colitis was induced by 2, 4‐dinitrobenzenesulfonic acid (DNBS). Colonic A2B receptor expression and localization were examined by RT‐PCR and immunofluorescence. The interaction between A2B receptors and adenosine deaminase was assayed by immunoprecipitation. The role of A2B receptors in the control of colonic motility was examined in functional experiments on longitudinal muscle preparations (LMPs). Key Results A2B receptor mRNA was present in colon from both normal and DNBS‐treated rats but levels were increased in the latter. A2B receptors were predominantly located in the neuromuscular layer, but, in the presence of colitis, were increased mainly in longitudinal muscle. Functionally, the A2B receptor antagonist MRS 1754 enhanced both electrically‐evoked and carbachol‐induced cholinergic contractions in normal LMPs, but was less effective in inflamed tissues. The A2B receptor agonist NECA decreased colonic cholinergic motility, with increased efficacy in inflamed LMP. Immunoprecipitation and functional tests revealed a link between A2B receptors and adenosine deaminase, which colocalize in the neuromuscular compartment. Conclusions and Implications Under normal conditions, endogenous adenosine modulates colonic motility via A2B receptors located in the neuromuscular compartment. In the presence of colitis, this inhibitory control is impaired due to a link between A2B receptors and adenosine deaminase, which catabolizes adenosine, thus preventing A2B receptor activation.